Efficacy of the small molecule inhibitor of Lipid II BAS00127538 against Acinetobacter baumannii - de Leeuw EPH (Dove Medical Press, 2014)
Erik PH de Leeuw Institute of Human Virology, University of Maryland School of Medicine, Baltimore, MD, USA Objective: To test the activity of a small molecule compound that targets Lipid II against Acinetobacter baumannii. Methods: Susceptibility to small molecule Lipid II inhibitor BAS00127538 was assessed using carbapenem- and colistin-resistant clinical isolates of A. baumannii. In addition, synergy between colisitin and this compound was assessed. Results: Small molecule Lipid II inhibitor BAS00127538 potently acts against A. baumannii and acts synergistically with colistin. Conclusion: For the first time, a compound that targets Lipid II is described that acts against multi-drug resistant isolates of A. baumannii. The synergy with colistin warrants further lead development of BAS00127538. Keywords: Lipid II, Acinetobacter baumannii, drug development